Pre-service English Teachers’ Use of Reinforcement Strategy in Microteaching - Esta Eradima Jonaria; Priyatno Ardi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This article investigates the reinforcement strategies used by pre-service English teachers in a microteaching class. The researchers employed a case study. Twenty-two students participated in this research. Observation, interviews, and video recording were used to gather the data. The data were then organized, coded, interpreted. The findings revealed that four types of reinforcement were used by pre-service English teachers in microteaching, namely positive reinforcement (81.93%), negative reinforcement (17%), punishment (3.36%), and extinction (2.94%). Moreover, the pre-service English teachers delivered reinforcement strategy by using warmth and enthusiasm expressions of praise, avoiding the punishment, and using non-variety usage of positive reinforcement. In conclusion, pre-service English teachers mostly used positive reinforcements in their teaching practice. They delivered the reinforcement strategy by using warmth and enthusiasm expressions of praise, avoiding the punishment, and using non-variety usage of positive reinforcement.